Cytotoxic Effect of Ethyl Acetate Fraction from the Aerial Parts of Jatropha Integerrima on the B16 Melanoma Cell - Mohamed-Ali, Marwa Jaafar; Ibrahim, Nabaa M. (Iraqi Journal of Science, 2026)
One plant with considerable therapeutic promise is Jatropha integerrima (J. integerrima ), which belongs to the Euphorbiaceae family. This study aimed to assess the cytotoxic effects on the (B16) melanoma cell line of ethyl acetate fraction obtained from the aerial parts of J. integerrima cultivated in Iraq, with six concentrations (200, 100, 50, 25, 12.5, and 6.25 µg/ml). It has drawn interest due to its possible cytotoxic effects on several cancer cell types. The bioactive chemicals responsible for the observed cytotoxic activity were analyzed qualitatively and quantitatively using High-Performance Liquid Chromatography (HPLC) on the ethyl acetate fraction. The cytotoxicity of the fraction was evaluated with the 3- [4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Five polyphenolic components classified as phenolic acids and flavonoids were found by phytochemical study of the J. integerrima ethyl acetate fraction. The ethyl acetate fraction with a high concentration of polyphenolic constituents showed the highest inhibition rate of 88.00% on the skin cancer (B16) cell line at a concentration of 200 µg/ml, with a significant difference as compared to the control sample during the 72-hour exposure period. Also, the values of half-maximal inhibitory concentration (IC50) of the fraction against the B16 cell lines were 27.35 µg/ml. J. integerrima plant has promising effects on cancerous lines, which calls for more in vitro and in vivo research.